1969
DOI: 10.1021/ja01048a059
|View full text |Cite
|
Sign up to set email alerts
|

Direct alkyl and aryl amination of heteroaromatic nitrogen compounds

Abstract: 5672size and charge distribution. This is supported by measurements of KI for the benzene-p-xylene system over a temperature range of 50" which indicate that AGO and AH" for the equilibrium are essentially the same, suggesting negligible contribution from differences in the entropy effects of solvation. The importance of solvation and ion pairing is, however, being explored more fully despite experimental difficulties attendant on the variation of solvent and cation due to the inherent susceptibility of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
24
0

Year Published

1974
1974
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 4 publications
1
24
0
Order By: Relevance
“…Apart from functional group interconversion and the formation of heterocycles, heteroatom nucleophiles have also been employed to mediate C-C-and (on exception) C-N-bond-forming rearrangements. In the context of secondary amides, early work dates back to 1969, when Abramovitch and Singer reported the N-pyridinylation of imidoyl chlorides with pyridine N-oxide 90 -a method that was optimised, generalised and mechanistically elucidated by Movassaghi et al some 40 years later (Scheme 22). 91 The products of heteroatom addition to keteniminium ions, taking the form of functionalised or substituted enol ethers, can be readily employed for [3,3]-sigmatropic rearrangements.…”
Section: Intermolecular Addition Of Heteroatom Nucleophilesmentioning
confidence: 99%
“…Apart from functional group interconversion and the formation of heterocycles, heteroatom nucleophiles have also been employed to mediate C-C-and (on exception) C-N-bond-forming rearrangements. In the context of secondary amides, early work dates back to 1969, when Abramovitch and Singer reported the N-pyridinylation of imidoyl chlorides with pyridine N-oxide 90 -a method that was optimised, generalised and mechanistically elucidated by Movassaghi et al some 40 years later (Scheme 22). 91 The products of heteroatom addition to keteniminium ions, taking the form of functionalised or substituted enol ethers, can be readily employed for [3,3]-sigmatropic rearrangements.…”
Section: Intermolecular Addition Of Heteroatom Nucleophilesmentioning
confidence: 99%
“…It has been previously shown that pyridine N -oxides are capable of yielding amides of 2-aminopyridines by reaction with imidoyl chlorides 4 or triflates 5 and 2-aminopyridines by reaction with isocyanates (Scheme 1). 6 Pyridine N -oxides activated with a phosphonium coupling reagent were shown to react with amines to give 2-aminopyridines by a Reissert− Henze-type reaction.…”
mentioning
confidence: 99%
“…9 We were interested in investigating the unexplored interaction of pyridine N -oxides and isocyanides, whose unique dual nature of reactivity, their tendency to react both as nucleophilic carbanions and electrophilic carbenes, has resulted in a rich chemical history. 10 Given that some pyridine N -oxide derivatives have shown poor or zero reactivity in prior methods, 4a,11 or were not reported in another, 7 we sought to expand the synthetic arsenal for the synthesis of 2-amino-pyridines. Also, some previously reported methods yield 2-aminopyridine amides as products that require harsh conditions to cleave the amide bond and isolate the desired 2-aminopyridine derivatives.…”
mentioning
confidence: 99%
See 2 more Smart Citations